The Filipino woman in Philippine miracle-themed films from 1970 to 2005 - Cabanawan, Erika Jean C. 1983-
"This study looks at the representation of the Filipino woman in Filipino miracle-themes films namely, Mga Mata ni Angelita (1978, Lauro Pacheco), Himala (1983, Ishmael Bernal), Tatarin (2001, Tikoy Aguiluz), Ang Huling Birhen sa Lupa (2003, Joel Lamangan), Santa Santita (2004, Laurice Guillen), and Birhen ng Manaoag (2005, Ben M7 Yalung). Each film is analyzed by reading religion and nation in identifying the image/s produced. Paul Schrader's analysis of the transcendental style in film and Mette Hjort's thematization of nation is used to analyze the way the Filipino miracle-themes film approaches religion and nation. The intersection of religion and nation in film provide the framework by which a feminist postcolonial analysis was built. Feminist postcolonial analysis, when applied to film, looks at the way women are represented and if they are subjected to the male or colonial gaze, if they are treated as the object or the subject, if they are active or passive, of if they remain colonized or are in the process of being decolonized in the context of hybrid religion that stems from a patriarchal and colonial system. The selected films reveal that while cinematic traditions abound in the Filipino miracle-themes film, there are opportunities for defiance and subversiveness in the backdrop of a postcolonial space. The selected films therefore produce images that traverse the spectrum of the stereotype and the supernatural. The evolving image of the female or female divine implicates the way we think about gender relations and roles in the context of postcoloniality."